Broad aggressive interactions among African carnivores suggest intraguild killing is driven by more than competition - Curveira-Santos, Gonçalo; Gigliotti, Laura; Silva, André P.; Sutherland, Chris; Foord, Stefan; Santos-Reis, Margarida; Swanepoel, Lourens H. (Ecology (Durham), 2022)
Theory on intraguild killing (IGK) is central to mammalian carnivore community ecology and top-down ecosystem regulation. Yet, the cryptic nature of IGK hinders empirical evaluations. Using a novel data source – online photographs of interspecific aggression between African carnivores – we revisited existing predictions about the extent and drivers of IGK. Compared with seminal reviews, our constructed IGK network yielded 10 more species and nearly twice as many interactions. The extent of interactions increased 37% when considering intraguild aggression (direct attack) as a precursor of killing events. We show that IGKoccurs over a wider range of body-mass ratios than predicted by standing competition-based views, with highly asymmetrical interactions being pervasive. Evidence that large species, particularly hypercarnivore felids, target sympatric carnivores with a wide range of body sizes suggests that current IGK theory is incomplete, underestimating alternative competition pathways and the role of predatory and incidental killing. Our findings reinforce the potential for IGK-mediated cascades in species-rich assemblages and community-wide suppressive effects of large carnivores.